Comorbidities in rheumatoid arthritis: analysis of hospital discharge records - G.S. Mela; T. Maio; L. Bensi; M. Parodi; M.A. Cimmino (PAGEPress Publications, 2011)
Objective: Arthritis is often associated with comorbidities. For many of them, such as hypertension, cardiovascular disease, chronic pulmonary disease, and upper gastrointestinal disease, arthritis and its treatment may also represent a risk factor. This study is concerned with an evaluation of the frequency of comorbidities in a cohort of patients with rheumatoid arthritis (RA). Methods: The discharge diagnoses of patients with RA during the period 1 January 1997 to 31 December 2000 were retrieved from the database of the Department of Internal Medicine of the University of Genova, Italy. The diagnosis of RA was made if the patient's discharge record contained the code 714 of the International Classification of Diseases, IX revision, as first 3 numbers. The other diagnoses were also recorded along with demographic data, type and duration of hospital stay, and performed procedures. Results: During the study period, 427 patients with RA were admitted to the hospital for a total number of 761 admissions, which represented 2.2% of total admissions. Ninety-one (21.3%) patients did not have comorbidities, whereas 336 (78.6%) had one or more comorbidities. The most frequently observed comorbidities were cardiovascular diseases (34.6%), including hypertension (14.5%) and angina (3.5%), followed by gastrointestinal (24.5%), genito-urinary (18.7%) and respiratory (17%) diseases. There was a male predominance (p=0.004) within patients with comorbidities, who were significantly older (64.2±3.2 years vs. 57.2±4.2 years; p<0.001) and required longer periods of hospital stay (22.7 days vs. 12.5 days; p<0.001). Conclusions: Comorbidities are present in nearly 80% of RA inpatients. Comorbidity is a good predictor of health outcome, health services utilization, and medical costs. Because RA comorbidity can act as confounder, it should be considered in epidemiologic studies and clinical trials.